Food Safety of Non-Animal Products in Constanta County: Results of Official Inspections in The First Quarter of 2023 - Iuliana CONDULET; Silvius STANCIU (Communications of International Proceedings, 2023)
This research has focused on the official inspection carried out by public institutions in Romania in the first quarter of 2023, in order to check the compliance of food products of non-animal origin with the legislative requirements in force, respectively the compliance with the food products’ hygiene requirements in accordance with the provisions in force. With the aim of detecting and eliminating from human consumption the food products that do not comply with the legal food safety requirements, in order to protect public health and consumer interests, as well as with the aim of uniformly applying the specific legislative requirements regarding food safety, official inspection actions and sampling were organized. This paper has demonstrated that the non-conformities found in relation to the taken samples and the carried-out inspections are found in a small percentage of the cases, thus indicating the fact that in Romania the economic operators know and apply the legislation in force. In view of the research, we can conclude that, on the Constanța County market, food products that are safe for consumption and of appropriate quality are being sold.
Keywords: ANSVSA; DSVSA Constanța; Inspection; Samples; First Quarter 2023